2013
DOI: 10.1037/a0031373
|View full text |Cite
|
Sign up to set email alerts
|

Fearful face detection sensitivity in healthy adults correlates with anxiety-related traits.

Abstract: Threatening faces have a privileged status in the brain, which can be reflected in a processing advantage. However, this effect varies among individuals, even healthy adults. For example, one recent study showed that fearful face detection sensitivity correlated with trait anxiety in healthy adults (Japee, Crocker, Carver, Pessoa, & Ungerleider, 2009). Here, we expanded upon those findings by investigating whether intersubject variability in fearful face detection is also associated with state anxiety, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
53
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(62 citation statements)
references
References 37 publications
4
53
5
Order By: Relevance
“…In line with recent studies (Doty, Japee, Ingvar, & Ungerleider, 2013; Japee et al, 2009), we found that healthy subjects displayed considerable variability in detecting threatening faces. However, unlike studies that have reported behavioral enhancement for threatening faces in the healthy population (e.g.…”
Section: Discussionsupporting
confidence: 93%
“…In line with recent studies (Doty, Japee, Ingvar, & Ungerleider, 2013; Japee et al, 2009), we found that healthy subjects displayed considerable variability in detecting threatening faces. However, unlike studies that have reported behavioral enhancement for threatening faces in the healthy population (e.g.…”
Section: Discussionsupporting
confidence: 93%
“…Unlike stimuli in the present study, threat-relevant stimuli in some prior investigations have been either backward-masked by neutral faces (e.g. [20]), or presented in an array of other emotional faces (e.g. [19]).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, when anxiety occurs outside the context of depression, it is robustly characterized by heightened vigilance towards threatening faces. For example, compared to healthy controls, individuals with anxiety disorders more often identify neutral or ambiguous facial expressions as negative and/or angry [17], recognize fearful faces more easily [18], and display an attentional bias towards fearful and angry faces [19, 20]. Anxious individuals also require less intensity of emotion than controls to recognize angry expressions [12].…”
Section: Introductionmentioning
confidence: 99%
“…9,10 Previous studies examining the association between neuroticism and facial emotion recognition in healthy individuals have found that certain emotion processing biases preceded the first depressive episode and could in part mediate the vulnerability to depression. 11,12 However, it remains unclear whether individuals scoring high on neuroticism show decreased processing of positive or increased processing of negative emotional information, or perhaps both. It is noteworthy that these studies often had moderate sample sizes and investigated only those subjects with the highest and lowest neuroticism scores (i.e.…”
Section: Introductionmentioning
confidence: 99%